Comparsion of participation Patterns between children with cerebral palsy and healthy children in out of school activities - Madineh Hassani; Afsoon Hassani Mehraban; Kazem hassani (Vesnu Publications, 2014)
Introduction: Participation in childhood everyday occupations is essential for health development of all children Regardless of ability or disability. The purpose of this study was Comparsion of participation patterrns between children with cerebral palsy and healthy children 7-15 years old.   Materials &Methods: In this cross-sectional study, 40 children with cerebral palsy from special education school and 40 healthy children from typical schools through simple non propebly sampling were selected. Participation was evaluated with the Children's Assessment of Participation and Enjoyment (CAPE). The data were analyzed by spss17.   Results: There were significant differences between children with cerebral palsy and health subject group in diversity and intensity for all of scales only recreational activities (p£0.001). children with CP participated in skill-based (p<0.001) and active physical activities alone than healthy children (p<0.01). children with CP participated proportionally less in places out of home than healthy subjects for most of activities (p£0.001). the main effects of gender and interaction effect between group type and gender was significant only in diversity of active physical activities CAPE variables (p<0.05).  Conclusion: The participation of health subjects in most activities was more than children with cerebral palsy. Cerebral palsy can affect participation patterns of children and youth in everyday activities.  Keywords: participation pattern, cerebral palsy, out of school activities